Solid electrolyte composition, and solid electrolyte membrane and all-solid-state battery comprising same

By using a carboxylic acid compound with a weight average molecular weight of 1000 to 5000 as a dispersant in the solid electrolyte composition of an all-solid state battery, the problem of poor uniformity of the solid electrolyte film thickness is solved, and high ionic conductivity and excellent battery performance are achieved.

CN119631213APending Publication Date: 2025-03-14LG ENERGY SOLUTION LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202480003370.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-20
Filing Date
2024-04-29
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The thickness uniformity of the solid electrolyte membrane in all-solid state batteries leads to a degradation of battery performance.

Method used

Carboxylic acid compounds having a weight average molecular weight of 1000 to 5000 are used as dispersants to inhibit agglomeration of solid electrolytes and improve their dispersion.

Benefits of technology

The uniform thickness and high ionic conductivity of the solid electrolyte membrane are achieved, and the performance and life of all-solid-state batteries are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119631213A_ABST
    Figure CN119631213A_ABST
Patent Text Reader

Abstract

The present invention relates to a solid electrolyte composition for an all-solid-state battery, a solid electrolyte membrane made therefrom, and an all-solid-state battery comprising the solid electrolyte membrane, the solid electrolyte composition comprising a solid electrolyte, a binder, a solvent, and a dispersant, in which the dispersant is a carboxylic acid compound having a weight average molecular weight of 1000 to 5000.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims priority to Korean Patent Application No. 10-2023-0078642, filed on Jun. 20, 2023, the disclosure of which is incorporated herein by reference in its entirety.

[0002] The present invention relates to a solid electrolyte composition, a solid electrolyte membrane comprising the same, and an all-solid-state battery. [Background technology]

[0003] Various batteries are being studied to overcome the limitations of current lithium secondary batteries in terms of capacity, safety, output, upsizing, and miniaturization.

[0004] Representative examples include: metal-air batteries with very high theoretical capacity compared to lithium secondary batteries; all-solid-state batteries that are safe and have no risk of explosion; supercapacitors in terms of output; NaS batteries or redox flow batteries (RFBs) for large-scale applications; and thin-film batteries for miniaturization. Academia and industry are conducting continuous research on these technologies.

[0005] All-solid-state batteries are batteries that replace the liquid electrolyte used in traditional lithium secondary batteries with solid electrolytes. Since no flammable solvents are used in the battery, there is no possibility of fire or explosion caused by the decomposition reaction of traditional electrolytes, which can greatly improve safety. In addition, since lithium (Li) metal or lithium alloy can be used as the negative electrode material, it has the advantage of significantly improving the energy density of the battery per unit mass and volume.

[0006] In order to improve the energy density of all-solid-state batteries, a solid electrolyte membrane must be made. The solid electrolyte membrane can be prepared by dispersing a solid electrolyte in a solvent to form a solid electrolyte composition in the form of a slurry, applying the composition to one side of a release film, drying it, and then removing the release film. In order to obtain a solid electrolyte membrane with uniform thickness, it is crucial to enhance the dispersion of the solid electrolyte in the composition, which is also closely related to the performance of the all-solid-state battery. If the solid electrolyte is not sufficiently dispersed in the composition, the thickness uniformity of the solid electrolyte membrane will be reduced, which may lead to degradation of the performance of the all-solid-state battery.

[0007] Therefore, there is a need to develop a solid electrolyte composition for an all-solid-state battery that can enhance the dispersion of the solid electrolyte.

[0008] [Prior art literature]

[0009] [Patent Document]

[0010] Korean Patent Application Publication No. 10-2021-0134748 [Summary of the invention]

[0011]

Technical issues

[0012] The present inventors have completed the present invention by confirming that the use of a carboxylic acid compound having a weight average molecular weight of 1,000 to 5,000 as a dispersant in a solid electrolyte composition for an all-solid-state battery can suppress agglomeration of the solid electrolyte in the composition and improve dispersibility. This has led to the completion of the present invention.

[0013] Therefore, an object of the present invention is to provide a solid electrolyte composition for an all-solid-state battery that can improve the dispersibility of a solid electrolyte.

[0014] In addition, an object of the present invention is to provide a solid electrolyte membrane having a uniform thickness and high ion conductivity by manufacturing a solid electrolyte membrane from the above-mentioned solid electrolyte composition.

[0015] Another object of the present invention is to provide an all-solid-state battery having excellent life characteristics by including the solid electrolyte membrane.

[0016]

Technical solution

[0017] To achieve the above object, the present invention provides a solid electrolyte composition for an all-solid-state battery, comprising a solid electrolyte, a binder and a dispersant, wherein the dispersant is a carboxylic acid compound having a weight average molecular weight of 1000 to 5000.

[0018] The present invention also provides a solid electrolyte membrane for an all-solid-state battery produced using the solid electrolyte composition of the present invention.

[0019] In addition, the present invention provides an all-solid-state battery, which comprises: a positive electrode, a negative electrode and a solid electrolyte membrane inserted therebetween, wherein the solid electrolyte membrane is the solid electrolyte membrane of the present invention.

[0020]

Beneficial Effects

[0021] The solid electrolyte composition for an all-solid-state battery of the present invention can inhibit agglomeration of the solid electrolyte in the composition and improve its dispersibility.

[0022] In addition, the solid electrolyte membrane produced using the solid electrolyte composition for an all-solid-state battery of the present invention can have a uniform thickness and high ion conductivity.

[0023] Furthermore, an all-solid-state battery including the solid electrolyte membrane of the present invention can have excellent performance.

Brief Description of the Drawings

[0024] Figure 1 This is a graph showing the dispersed particle size distribution of the solid electrolyte in the solid electrolyte composition for an all-solid-state battery of Experimental Example 1.

[0025] Figure 2 Graph showing the life characteristics of the all-solid-state battery of Experimental Example 3. [Specific implementation method]

[0026] Hereinafter, the present invention will be described in more detail.

[0027] The terms and words used in this specification and claims should not be interpreted as their ordinary meanings or dictionary meanings, but should be interpreted as meanings and concepts consistent with the technical idea of ​​the present invention based on the principle that the inventor can appropriately define the concepts of the terms in order to best explain his invention.

[0028] The terms used in this specification are only used to illustrate specific examples and are not intended to limit the present invention. Unless the context clearly indicates otherwise, expressions in the singular include plural forms. In the present invention, the terms "comprising" or "having" are intended to specify the presence of the features, numbers, steps, operations, ingredients, parts or combinations thereof described in this specification, and are not intended to exclude the possibility of the presence or addition of one or more other features, numbers, steps, operations, ingredients, parts or combinations thereof.

[0029] Solid electrolyte composition for all-solid-state battery

[0030] The present invention relates to a solid electrolyte composition for an all-solid-state battery, wherein the solid electrolyte composition for an all-solid-state battery comprises a solid electrolyte, a binder and a dispersant, and the dispersant is a carboxylic acid compound having a weight average molecular weight (Mw) of 1000 to 5000.

[0031] Conventional solid electrolyte compositions for all-solid-state batteries do not contain dispersants, which can cause solid electrolytes to agglomerate within the composition. If the solid electrolyte agglomerates, the dispersed particle size of the solid electrolyte in the solid electrolyte composition for all-solid-state batteries increases. If the dispersed particle size of the solid electrolyte increases, the thickness of the solid electrolyte film for all-solid-state batteries manufactured using the solid electrolyte composition becomes uneven, resulting in a decrease in the performance of the all-solid-state battery containing the film.

[0032] The solid electrolyte composition for an all-solid-state battery of the present invention uses a carboxylic acid compound having a weight average molecular weight of 1000 to 5000 as a dispersant in the composition, which can inhibit the agglomeration of the solid electrolyte in the composition, improve the dispersibility of the solid electrolyte, and has excellent solubility in a solvent. As a result, a solid electrolyte membrane for an all-solid-state battery having a uniform thickness and excellent ionic conductivity can be provided.

[0033] If the carboxylic acid compound is not used, the dispersibility of the solid electrolyte may deteriorate, therefore, it is preferred to use the carboxylic acid compound as a dispersant to improve the dispersibility of the solid electrolyte. In addition, if the weight average molecular weight of the carboxylic acid compound is less than 1000, its solubility in a solvent is excellent, but the aggregation control of the solid electrolyte is poor, which may cause the agglomeration of the solid electrolyte. On the contrary, if the weight average molecular weight of the carboxylic acid compound exceeds 5000, it may have excellent aggregation control of the solid electrolyte, but the solubility in the solvent is poor. As a result, a solid electrolyte membrane for an all-solid-state battery with uneven thickness may be obtained, which may deteriorate the performance of the all-solid-state battery comprising the solid electrolyte membrane.

[0034] The dispersant may include one or more selected from the group consisting of glycolic acid ethoxylate lauryl ether, glycolic acid ethoxylate oleyl ether, and glycolic acid ethoxylate 4-tert-butylphenyl ether.

[0035] Based on the total weight of the solid electrolyte composition for all-solid-state batteries, the content of the dispersant in the composition can be 0.1 to 2 weight %, preferably 0.1 to 0.7 weight %. Within this range, the dispersibility of the solid electrolyte can be improved. If the content of the dispersant is less than 0.1 weight %, the improvement of the dispersibility of the solid electrolyte cannot be expected. If its content exceeds 2 weight %, the content of the solid electrolyte will be reduced, which may lead to performance degradation of the all-solid-state battery.

[0036] The solid electrolyte composition for all-solid-state batteries of the present invention contains the dispersant as described above, which can improve the dispersibility of the solid electrolyte in the solid electrolyte composition and inhibit agglomeration. Therefore, the solid electrolyte can exist in the solid electrolyte composition for all-solid-state batteries without agglomeration.

[0037] Solid electrolyte particle size D 50 The particle size D can be 0.5 to 1.5 μm. 99 It can be 3 to 5 μm. Preferably, the particle size D 50 The particle size D can be 0.6 to 1.1 μm. 99 It can be 3 to 4 μm.

[0038] Dispersed particle size D of solid electrolyte in solid electrolyte composition for all-solid-state battery 50 The dispersed particle size D can be 0.5 to 1.5 μm. 99 It can be 3 to 5 μm. More specifically, when the particle size D is used 50 0.5 to 1.5 μm and the particle size D 99 When a solid electrolyte having a particle size of 3 to 5 μm is used as a solid electrolyte composition for an all-solid-state battery, the dispersed particle size D of the solid electrolyte in the composition is 50 It can be 0.5 to 1.5 μm, and the dispersed particle size D99 It can be 3 to 5 μm. In other words, the particle size of the solid electrolyte before dispersion can be made the same as the dispersed particle size of the solid electrolyte after dispersion. Therefore, the solid electrolyte can exist in the solid electrolyte composition for an all-solid-state battery in a dispersed form without agglomeration.

[0039] In the present specification, the dispersed particle size may refer to the particle size of the solid electrolyte dispersed in the solid electrolyte composition for an all-solid-state battery.

[0040] If the solid electrolyte composition for an all-solid-state battery does not contain a dispersant, or if the weight average molecular weight of the carboxylic acid compound dispersant is less than 1000 or exceeds 5000, the particle size D 99 The dispersed particle size D of the solid electrolyte in the solid electrolyte composition for all-solid-state batteries is 3 to 5 μm 99 May exceed 5μm. In other words, since the dispersibility is not improved, the solid electrolyte may agglomerate. However, if a carboxylic acid compound with a weight average molecular weight of 1000 to 5000 is included as a dispersant, the particle size of the solid electrolyte and the dispersed particle size in the solid electrolyte composition for all-solid-state batteries can be the same. That is, by containing the above-mentioned dispersant, the solid electrolyte composition for all-solid-state batteries of the present invention can prevent the agglomeration of the solid electrolyte in the composition and improve the dispersibility. In other words, the solid electrolyte can be well dispersed in the solid electrolyte composition for all-solid-state batteries without agglomeration, maintaining its particle size. Therefore, the particle size of the solid electrolyte can be the same or similar to the dispersed particle size.

[0041] Therefore, in the solid electrolyte composition for all-solid-state batteries, the dispersed particle size D of the solid electrolyte is 99 and dispersed particle size D 50 The ratio can be 2 to 7, preferably 3 to 6.

[0042] The solid electrolyte may include one or more selected from the group consisting of a sulfide-based solid electrolyte, a polymer-based solid electrolyte, and an oxide-based solid electrolyte, and preferably includes a sulfide-based solid electrolyte.

[0043] The sulfide-based solid electrolyte includes sulfur (S), has ion conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, and may include Li-PS-based glass or Li-PS-based glass ceramics.

[0044] Specifically, the sulfide-based solid electrolyte may include one or more selected from the group consisting of: Li 6 PS 5 Cl, Li 6 PS 5 Br, Li 6 PS 5 I. Li 2SP 2 S 5 , Li 2 S-LiI-P 2 S 5 , Li 2 S-LiI-Li 2 OP 2 S 5 , Li 2 S-LiBr-P 2 S 5 , Li 2 S-Li 2 OP 2 S 5 , Li 2 S-Li 3 PO 4 -P 2 S 5 , Li 2 SP 2 S 5 -P 2 S 5 , Li 2 SP 2 S 5 -SiS 2 , Li 2 SP 2 S 5 -SnS、Li 2 SP 2 S 5 -Al 2 S 3 , Li 2 S-GeS 2 and Li 2 S-GeS 2 -ZnS. Preferably, it may include one or more selected from the group consisting of: Li 6 PS 5 Cl, Li 6 PS 5 Br and Li 6 PS 5 I. The Li 6 PS 5 Cl, Li 6 PS 5 Br and Li 6 PS 5 I can be a argyrodite-type solid electrolyte. In addition, the sulfide solid electrolyte can be in the form of a doped trace element, such as Li doped with bromine (Br). 6 PS 5 Cl.

[0045] The polymer solid electrolyte is a composite of lithium salt and polymer resin, that is, a type of polymer electrolyte material formed by adding polymer resin to solvated lithium salt. It can exhibit a conductivity of about 1×10 -7 S / cm or more, preferably about 1×10 -5 S / cm or more.

[0046] The non-limiting examples of the polymer resin can include at least one of polyether polymers, polycarbonate polymers, acrylate polymers, polysiloxane polymers, phosphazene polymers, polyethylene derivatives, oxyalkylene derivatives (such as polyethylene oxide), phosphate polymers, polyethylenimine, polyester thioether, polyvinyl alcohol, polyvinylidene fluoride or polymers containing ion dissociable groups. In addition, the polymer electrolyte can include one or more of branched copolymers, comb-like polymer resins and cross-linked polymer resins as comonomers of amorphous polymers such as PMMA, polycarbonate, polysiloxane (PDMS) and / or phosphazenes as polymer resins and PEO (polyethylene oxide) main chain copolymers.

[0047] In the polymer solid electrolyte, the lithium salt can be represented by Li + X - The anion of the lithium salt is not particularly limited, but may include F - , Cl - Br - ,I - 、NO 3 - 、N(CN) 2 - , BF 4 - , ClO 4 - PF 6 - ,(CF 3 ) 2 PF 4 - ,(CF 3 ) 3 PF 3 - ,(CF 3 ) 4 PF 2 - ,(CF 3 ) 5 PF - ,(CF 3 ) 6 P - CF 3 SO 3- CF 3 CF 2 SO 3 - ,(CF 3 SO 2 ) 2 N - 、(FSO 2 ) 2 N - CF 3 CF 2 (CF 3 ) 2 CO - ,(CF 3 SO 2 ) 2 CH - , (SF 5 ) 3 C - ,(CF 3 SO 2 ) 3 C - CF 3 (CF 2 ) 7 SO 3 - CF 3 CO 2 - , CH 3 CO 2 - 、SCN - ,(CF 3 CF 2 SO 2 ) 2 N - wait.

[0048] The oxide-based solid electrolyte may contain oxygen (O) and possess ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table. For example, it may include one or more selected from the group consisting of: LLTO compounds, Li 6 La 2 CaTa 2 O 12 , Li 6 La 2 ANb 2 O 12 (where A is Ca or Sr), Li 2 Nd 3 T8h 12 , Li 3 BO 2.5 N0.5 , Li 9 SiAlO 8 , LAGP compounds, LATP compounds, Li 1+x Ti 2-x Al x Si y (PO 4 ) 3-y (where 0≤x≤1, 0≤y≤1), LiAl x Zr 2-x (PO 4 ) 3 (where 0≤x≤1, 0≤y≤1), LiTi x Zr 2-x (PO 4 ) 3 (wherein 0≤x≤1, 0≤y≤1), LISICON compounds, LIPON compounds, perovskite compounds, NASICON compounds and LLZO compounds.

[0049] The solid electrolyte may be included in an amount of 95 wt % to 99 wt % based on the total weight of the solid electrolyte composition for an all-solid-state battery.

[0050] The type of adhesive is not limited to a specific type as long as it is used in the art.

[0051] For example, nitrile rubber (NBR), styrene butadiene rubber (SBR), butadiene rubber (BR), styrene-butadiene-styrene copolymer (SBS), polybutadiene (PAN), styrene-ethylene / butylene-styrene block copolymer (SEBS), silicone rubber (SR), hydrogenated nitrile rubber (HNBR), polyethylene-vinyl acetate (PEVA), polymethyl methacrylate (PMMA), polyisobutylene (PIB), polyacrylate, etc. can be used, but are not limited to these. In the present invention, styrene-butadiene-styrene copolymer can be preferred.

[0052] The binder may be included in an amount of 0.5 wt % to 5 wt % based on the total weight of the solid electrolyte composition for an all-solid-state battery.

[0053] The solid electrolyte composition for an all-solid-state battery of the present invention may be in the form of a slurry in which a solid electrolyte, a binder, and a dispersant are dispersed in a solvent.

[0054] The solvent is not particularly limited as long as it can disperse the solid electrolyte, the binder, and the dispersant. Examples include xylene, hexane, benzene, anisole, isobutyl isobutyrate, toluene, and butyl butyrate.

[0055] Solid electrolyte membrane for all-solid-state batteries

[0056] The present invention also relates to a solid electrolyte membrane for an all-solid-state battery produced using the solid electrolyte composition for an all-solid-state battery.

[0057] The solid electrolyte membrane for an all-solid-state battery may be manufactured by applying the solid electrolyte composition for an all-solid-state battery to one side of a release film, drying, and then removing the release film.

[0058] The solid electrolyte composition for all-solid-state batteries shows excellent dispersibility and no agglomeration in the composition. Therefore, when the composition is used to manufacture a solid electrolyte membrane for an all-solid-state battery, a solid electrolyte membrane with uniform thickness and excellent ionic conductivity can be manufactured. In the present invention, the thickness of the solid electrolyte membrane for an all-solid-state battery can be 20 to 50 μm. In addition, the ionic conductivity of the solid electrolyte membrane for an all-solid-state battery can be 1.3×10 -3 The ionic conductivity may be the ionic conductivity measured at room temperature (25° C.).

[0059] All-solid-state battery

[0060] In addition, the present invention relates to an all-solid-state battery, comprising: a positive electrode, a negative electrode and a solid electrolyte membrane interposed therebetween. The solid electrolyte membrane may be the above-mentioned solid electrolyte membrane for an all-solid-state battery of the present invention.

[0061] An all-solid-state battery can be a lithium secondary battery with no restrictions on the positive and negative electrodes, and can be a lithium-air battery, a lithium oxide battery, a lithium-sulfur battery, or a lithium metal battery.

[0062] The positive electrode may include a positive electrode collector and a positive electrode active material layer coated on one side or both sides of the positive electrode collector.

[0063] The purpose of the positive electrode collector is to support the positive electrode active material layer, without particular limitation, as long as it has excellent electrical conductivity and is electrochemically stable within the voltage range of the lithium secondary battery. For example, the positive electrode collector can be any metal selected from the group consisting of copper, aluminum, stainless steel, titanium, silver, palladium, nickel, its alloys and combinations thereof. Stainless steel can be surface treated with carbon, nickel, titanium or silver. Preferably, aluminum-cadmium alloy can be used as the alloy. In addition, sintered carbon, non-conductive polymers surface treated with conductive materials, or conductive polymers can also be used.

[0064] The positive electrode current collector can improve its bonding strength with the positive electrode active material by forming fine concavoconvexities on its surface. It can be used in various forms such as film, sheet, foil, screen, net, porous body, foam or non-woven fabric.

[0065] The positive electrode active material layer may include a positive electrode active material, and may optionally contain a conductive material and a binder.

[0066] The positive electrode active material may vary depending on the type of all-solid-state battery. For example, the positive electrode active material may include, but is not limited to, the following compounds: layered compounds, such as lithium cobalt oxide (LiCoO 2 ) and lithium nickel oxide (LiNiO 2 ), or a compound substituted with one or more transition metals; lithium manganese oxide, such as Li 1+x Mn 2-x O 4 (where 0≤x≤0.33), LiMnO 3 、LiMn 2 O 3 and LiMnO 2 Lithium manganese oxide; lithium copper oxide (Li 2 CuO 2 ); Vanadium oxides, such as LiV 3 O 8 、V 2 O 5 and Cu 2 V 2 O 7 Formula LiNi 1-x M x O 2 (wherein M = Co, Mn, Al, Cu, Fe, Mg, B or Ga; 0.01≤x≤0.3) represented by a nickel-type lithium nickel oxide; formula LiMn 2-x M x O 2 (wherein M = Co, Ni, Fe, Cr, Zn or Ta; 0.01≤x≤0.1) or Li 2 Mn 3 MO 8 (wherein M = Fe, Co, Ni, Cu or Zn) represented by a lithium manganese composite oxide; formula LiNi x Mn 2-x O 4 Spinel structure lithium manganese composite oxide; LiCoPO 4 ;LiFePO 4 ; and sulfur compounds, such as elemental sulfur (S 8 )、Li 2 S n (n=1), organic sulfur compounds or carbon sulfur polymers ((C 2 S x ) n :x=2.5~50,n=2).

[0067] The conductive material is a material that electrically connects the electrolyte and the cathode active material and serves as a path for electrons to move from the collector to the cathode active material, and can be used without limitation as long as it does not cause chemical changes in the lithium secondary battery and has porosity and conductivity.

[0068] For example, the conductive material can be a porous carbon material. Such carbon materials include carbon black, graphite, graphene, activated carbon, carbon fiber, etc. It can also be a metal fiber such as a metal mesh; a metal powder such as copper, silver, nickel, aluminum, etc.; or an organic conductive material such as a polyphenylene derivative. These conductive materials can be used alone or in combination.

[0069] Currently, commercially available conductive materials include acetylene black series (products of Chevron Chemical Company or Gulf Oil Company), Ketjen Black EC series (product of Armak Company), Vulcan XC-72 (product of Cabot Company) and Super P (product of MMM). Examples include acetylene black, carbon black and graphite.

[0070] In addition, the binder can enhance the bonding strength between components constituting the positive electrode and between these components and the current collector, and any binder known in the art can be used.

[0071] For example, the adhesive may include a mixture or copolymer of one or more selected from the group consisting of: a fluororesin adhesive, such as polyvinylidene fluoride (PVdF) or polytetrafluoroethylene (PTFE); a rubber adhesive, such as styrene-butadiene rubber (SBR), nitrile rubber or styrene-isoprene rubber; a cellulose adhesive, such as carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose or regenerated cellulose; a polyol adhesive; a polyolefin adhesive, such as polyethylene or polypropylene; a polyimide adhesive; a polyester adhesive; and a silane adhesive.

[0072] The negative electrode may include a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector. In addition, similar to the positive electrode, the negative electrode may contain a conductive material and a binder when necessary. In this case, the negative electrode current collector, the conductive material and the binder are as described above.

[0073] The negative electrode active material can be any material that can reversibly insert or remove lithium ions (Li + ) or a material that can reversibly react with lithium ions to form a lithium-containing compound.

[0074] For example, the negative electrode active material may include, but is not limited to, one or more selected from the group consisting of crystalline artificial graphite, crystalline natural graphite, amorphous hard carbon, low crystalline soft carbon, carbon black, acetylene black, Ketjen black, Super-P, graphene and fibrous carbon, one or more carbon-based materials, silicon-based materials such as Lix Fe 2 O 3 (where 0 ≤ x ≤ 1), Li x WO 2 (where 0 ≤ x ≤ 1) and Sn x Me 1-x Me' y O z (where Me: Mn, Fe, Pb, Ge; Me': Al, B, P, Si, elements in Groups 1, 2, and 3 of the periodic table, halogens; 0 < x ≤ 1; 1 ≤ y ≤ 3; 1 ≤ z ≤ 8) and other metal composite oxides; lithium metal; lithium alloys; silicon-based alloys; tin-based alloys; such as SnO, SnO 2 、PbO、PbO 2 、Pb 2 O 3 、Pb 3 O 4 、Sb 2 O 3 、Sb 2 O 4 、Sb 2 O 5 、GeO、GeO 2 、Bi 2 O 3 、Bi 2 O 4 and Bi 2 O 5 and other metal oxides; conductive polymers such as polyacetylene; Li-Co-Ni-based materials; titanium oxide; and lithium titanium oxide.

[0075] In addition, the negative electrode may include a negative electrode current collector and a coating containing metal-carbon composite particles located on the negative electrode current collector. This may refer to a negative electrode configuration that does not include a conventional negative electrode active material.

[0076] During the charging process of the all-solid-state battery, by passing lithium ions through the coating and reaching the surface of the negative electrode current collector for deposition, a lithium metal layer can be formed on the negative electrode.

[0077] The metal-carbon composite particles may be carbon particles and metal particles attached to or coated with each other, and they may be physically bonded or chemically bonded.

[0078] The carbon particles may include natural graphite, artificial graphite, hard carbon, soft carbon, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal cracking carbon black, carbon nanotubes, fullerenes, carbon fibers, and fluorinated carbon.

[0079] The metal particles are lithium-philic metals, such as Ni, Cu, Ag, Au, Pt, Al, Zn and Bi, and can be a combination of one or more of these metals. The introduction of these lithium-philic metals helps to form a stable and uniform lithium layer on the surface of the collector.

[0080] The negative electrode can be manufactured by mixing a binder solution with composite particles to prepare a coating layer-forming slurry, applying the slurry to a negative electrode collector, and drying. The binder used may be any conventional binder commonly used in the art.

[0081] The present invention has no particular limitation on the manufacture of all-solid-state batteries, and known methods can be used.

[0082] For example, a solid electrolyte membrane is provided between the positive electrode and the negative electrode, and the battery cell is assembled by compression molding. The assembled battery cell is installed in an outer packaging material and sealed by heating and compression. The outer packaging material may be a laminated package of aluminum, stainless steel, etc., or a metal container such as a cylindrical or square container.

[0083] For example, the positive and negative electrodes are prepared by a slurry coating process of preparing a slurry composition including a corresponding electrode active material, a solvent, and a binder, coating, and then drying.

[0084] The method of coating the electrode slurry on the current collector may include distributing the electrode slurry on the current collector and uniformly dispersing it using a scraper, die casting, comma coating or screen printing, etc. In addition, the electrode slurry may be formed on a separate substrate and then bonded to the current collector by pressing or laminating. In this case, the final coating thickness can be controlled by adjusting the concentration of the slurry solution or the number of coatings.

[0085] The drying process is a process of removing solvent and moisture from the slurry to dry the slurry coated on the metal collector, which may vary depending on the solvent used. For example, it can be carried out in a vacuum oven at 50 to 200° C. Drying methods include, for example, drying by warm air, hot air, low humidity air, vacuum drying, irradiation with (far) infrared or electromagnetic radiation, etc. The drying time is not particularly limited, but is generally in the range of 30 seconds to 24 hours.

[0086] After the drying process, a cooling step may be further included, wherein the cooling step may include slowly cooling to room temperature to ensure that a recrystallized structure of the binder is well formed.

[0087] In addition, if necessary, in order to increase the capacity density of the electrode after the drying process and improve the adhesion between the collector and the active material, a calendering process may be performed. The process includes passing the electrode between two heated rollers to compress it to a desired thickness. The present invention has no particular restrictions on the calendering process, and a known pressing method may be used. For example, it may be performed by passing the electrode between rotating rollers or using a flat press.

[0088] The shape of the all-solid-state battery is not particularly limited and can be various forms such as cylindrical, stacked, coin-shaped, etc.

[0089] [Example]

[0090] In the following, preferred embodiments of the present invention are described for the purpose of illustrating the present invention, however, it is obvious to those skilled in the art that various changes and modifications can be made within the scope of the present invention and the technical idea, and such changes and modifications fall within the scope of the attached patent claims.

[0091] Example 1

[0092] Example 1-1. Preparation of solid electrolyte composition for all-solid-state battery

[0093] The solid electrolyte composition for all-solid-state batteries in the form of a slurry of Example 1-1 was prepared in the following manner: the particle size (D 50 ) is 0.6 to 0.8 μm and the particle size (D 99 ) is 3 to 4 μm argyrodite (Li 6 PS 5 Cl), styrene-butadiene-styrene copolymer as a binder and glycolic acid ethoxylate lauryl ether with a weight average molecular weight of 4080 as a dispersant were mixed in a weight ratio of 98:1.7:0.3, and then the mixture was added to isobutyl isobutyrate.

[0094] Example 1-2. Production of solid electrolyte membrane for all-solid-state battery

[0095] Polyethylene terephthalate was used as a release film. The solid electrolyte composition prepared in Example 1-1 was coated on the release film using a rod coater. It was then dried under vacuum for 5 hours, and the release film was removed, thereby obtaining the solid electrolyte membrane for an all-solid-state battery of Example 1-2.

[0096] Examples 1-3

[0097] The positive electrode is manufactured by the following method: positive electrode active material (NCM 811), conductive material (carbon fiber), solid electrolyte (Li 6 PS 5C1) and a binder (polytetrafluoroethylene) were mixed in a weight ratio of 84:0.2:14.8:1, and then the mixture was coated on a positive electrode collector and rolled.

[0098] The negative electrode was prepared by applying a mixture of a negative electrode active material (carbon black) and a binder (polyvinylidene fluoride) to a thickness of 20 μm on SUS having a thickness of 10 μm as a negative electrode collector.

[0099] The solid electrolyte membrane prepared in Example 1-2 was inserted between the positive electrode and the negative electrode to manufacture the all-solid-state battery of Example 1-3.

[0100] Example 2

[0101] Except for using glycolic acid ethoxylate oleyl ether with a weight average molecular weight of 2220 as a dispersant, the solid electrolyte composition for an all-solid-state battery of Example 2-1, the solid electrolyte membrane for an all-solid-state battery of Example 2-2 and the all-solid-state battery of Example 2-3 were prepared according to the procedures of Examples 1-1, 1-2 and 1-3.

[0102] Example 3

[0103] Except for using glycolic acid ethoxylate 4-tert-butylphenyl ether with a weight average molecular weight of 1080 as a dispersant, the solid electrolyte composition for an all-solid-state battery of Example 3-1, the solid electrolyte membrane for an all-solid-state battery of Example 3-2 and the all-solid-state battery of Example 3-3 were prepared according to the processes of Examples 1-1, 1-2 and 1-3.

[0104] Comparative Example 1

[0105] The solid electrolyte composition for an all-solid-state battery of Comparative Example 1-1, the solid electrolyte membrane for an all-solid-state battery of Comparative Example 1-2, and the all-solid-state battery of Comparative Example 1-3 were prepared according to the procedures of Examples 1-1, 1-2, and 1-3 except that no dispersant was used.

[0106] Comparative Example 2

[0107] Except for using glycolic acid ethoxylate lauryl ether with a weight average molecular weight of 740 as a dispersant, the solid electrolyte composition for an all-solid-state battery of Comparative Example 2-1, the solid electrolyte membrane for an all-solid-state battery of Comparative Example 2-2, and the all-solid-state battery of Comparative Example 2-3 were prepared according to the procedures of Examples 1-1, 1-2 and 1-3.

[0108] Comparative Example 3

[0109] Except for using glycolic acid ethoxylate oleyl ether with a weight average molecular weight of 5680 as a dispersant, the solid electrolyte composition for an all-solid-state battery of Comparative Example 3-1, the solid electrolyte membrane for an all-solid-state battery of Comparative Example 3-2 and the all-solid-state battery of Comparative Example 3-3 were prepared according to the procedures of Examples 1-1, 1-2 and 1-3.

[0110] Experimental Example 1. Measurement of Dispersed Particle Size of Solid Electrolyte in Solid Electrolyte Composition for All-Solid State Batteries

[0111] The dispersed particle diameters of the solid electrolytes in the solid electrolyte compositions for all-solid-state batteries in Examples 1-1 to 3-1 and Comparative Examples 1-1 to 3-1 were measured using a particle size analyzer.

[0112] The solid electrolytes used in Examples 1-1 to 3-1 and Comparative Examples 1-1 to 3-1 had a particle size (D 50 ) is 0.6 to 0.8 μm and the particle size (D 99 ) is 3 to 4 μm argyrodite (Li 6 PS 5 Cl). The dispersed particle size is measured to confirm that the solid electrolyte is well dispersed in the solid electrolyte composition for an all-solid-state battery without agglomeration.

[0113] The results are shown in Table 1 and Figure 1 .

[0114]

Table 1

[0115] Example 1-1 Example 2-1 Example 3-1 Comparative Example 1-1 Comparative Example 2-1 Comparative Example 3-1 <![CDATA[D 10 ]]> 0.275μm 0.171μm 0.144μm 0.42μm 0.17μm 0.227μm <![CDATA[D 50 ]]> 1.01μm 0.693μm 0.603μm 0.875μm 0.733μm 0.815μm <![CDATA[D 90 ]]> 2.25μm 2.03μm 1.59μm 3.64μm 2.43μm 2.74μm <![CDATA[D 95 ]]> 2.66μm 2.63μm 2.05μm 18.2μm 3.39μm 3.79μm <![CDATA[D 99 ]]> 3.46μm 3.86μm 3.02μm 33.6μm 6.18μm 11.4μm <![CDATA[D 99 / D 50 ]]> 3.43 5.57 5.01 38.4 8.43 13.99 <![CDATA[D 95 / D 50 ]]> 2.63 3.8 3.4 20.8 4.62 4.65

[0116] Table 1 shows that in the solid electrolyte compositions for all-solid-state batteries of Examples 1-1 to 3-1, the dispersed particle size (D 50 and D 99 ) value and the particle size of the solid electrolyte before dispersion (D 50 and D 99 This indicates that the solid electrolyte is well dispersed in the composition without agglomeration.

[0117] Comparative Example 1-1 containing no dispersant, Comparative Example 2-1 using a carboxylic acid compound with a weight average molecular weight of less than 1000 as a dispersant, and Comparative Example 3-1 using a carboxylic acid compound with a weight average molecular weight of more than 5000 as a dispersant showed that the solid electrolyte in the solid electrolyte composition for all-solid-state batteries was significantly agglomerated and the particle size could not be maintained. This resulted in a dispersed particle size (D 99 ) increased significantly. In particular, in Comparative Example 1-1 without a dispersant, the agglomeration of the solid electrolyte was most obvious, resulting in a dispersed particle size (D 99 ) is greatly increased. Even if a dispersant is included, if the weight average molecular weight of the carboxylic acid compound exceeds the range of 1000 to 5000, the dispersion of the solid electrolyte is ineffective, resulting in a dispersed particle size (D99 ) increases. Therefore, Comparative Examples 1-1 to 3-1 confirm that the dispersed particle size (D 99 ) indicates that agglomeration of the solid electrolyte has occurred.

[0118] Experimental Example 2. Measurement of ionic conductivity of solid electrolyte membrane for all-solid-state battery

[0119] The thickness of the solid electrolyte membrane for an all-solid-state battery of Examples 1-2 to 3-2 and Comparative Examples 1-2 to 3-2 was 30 μm, and the ion conductivity of the solid electrolyte membrane for an all-solid-state battery was measured.

[0120] The ionic conductivity was measured by placing aluminum foil on the upper and lower parts of the solid electrolyte membrane for the all-solid-state battery, assembling a jig cell, and then pressurizing at 360 MPa. The results are shown in Table 2 below.

[0121]

Table 2

[0122] Ionic conductivity (S / cm) Example 1-2 <![CDATA[1.41×10 -3 ]]> Example 2-2 <![CDATA[1.36×10 -3 ]]> Example 3-2 <![CDATA[1.32×10 -3 ]]> Comparative Example 1-2 <![CDATA[1.02×10 -3 ]]> Comparative Example 2-2 <![CDATA[1.09×10 -3 ]]> Comparative Example 3-2 <![CDATA[1.04×10 -3 ]]>

[0123] Examples 1-2 to 3-2 use a carboxylic acid compound having a weight average molecular weight of 1000 to 5000 as a dispersant, and exhibit high ion conductivity of the solid electrolyte membrane.

[0124] Comparative Example 1-2 does not contain a dispersant, Comparative Example 2-2 uses a carboxylic acid compound with a weight average molecular weight of less than 1000 as a dispersant, and Comparative Example 3-2 uses a carboxylic acid compound with a weight average molecular weight of more than 5000 as a dispersant. It can be seen from the results of Experimental Example 1 that the solid electrolyte in the solid electrolyte composition for all-solid-state batteries of Comparative Examples 1-1 to 3-1 is not well dispersed, and agglomeration is observed. Therefore, when it is used to manufacture a solid electrolyte membrane for all-solid-state batteries, it is found that the thickness is uneven and the ionic conductivity of the solid electrolyte membrane for all-solid-state batteries is low. In the case of Comparative Example 1-2, the dispersion of the solid electrolyte is very poor, resulting in agglomeration of the solid electrolyte. However, since there is no dispersant, the content of the solid electrolyte increases, so the ionic conductivity is similar to Comparative Examples 2-2 and 3-2.

[0125] Experimental Example 3. Evaluation of Life Characteristics of All-Solid-State Batteries

[0126] The life characteristics of the all-solid-state batteries of Examples 1-3 to 3-3 and Comparative Examples 1-3 to 3-3 were measured.

[0127] The life characteristics were measured by charging the all-solid-state battery at 0.33C to 4.25V in CCCV mode at 60°C, then discharging to 3.0V at a constant current for 150 charge and discharge cycles, and determining the capacity retention rate.

[0128] The results are shown in Figure 2 .

[0129] Examples 1-3 to 3-3 use a carboxylic acid compound having a weight average molecular weight of 1000 to 5000 as a dispersant and show excellent life characteristics of the all-solid-state battery.

[0130] Comparative Example 1-1 does not contain a dispersant, Comparative Example 2-1 uses a carboxylic acid compound with a weight average molecular weight of less than 1000 as a dispersant, and Comparative Example 3-1 uses a carboxylic acid compound with a weight average molecular weight of more than 5000 as a dispersant. It can be seen from the results of Experimental Example 1 that the solid electrolytes in the solid electrolyte compositions for all-solid-state batteries of Comparative Examples 1-1 to 3-1 are not well dispersed, and agglomeration is observed. Therefore, it can be seen from the results of Experimental Example 2 that the thickness of the solid electrolyte membranes for all-solid-state batteries of Comparative Examples 1-2 to 3-2 is uneven and the ionic conductivity is low. Therefore, it was found that when these are used to manufacture all-solid-state batteries, the life characteristics of the all-solid-state batteries are very poor.

[0131] The present invention relates to a solid electrolyte composition for an all-solid-state battery using a carboxylic acid compound having a weight average molecular weight of 1000 to 5000 as a dispersant, wherein the solid electrolyte does not agglomerate in the composition due to the dispersant and is effectively dispersed. In addition, a solid electrolyte membrane for an all-solid-state battery made of the solid electrolyte composition has a uniform thickness and high ion conductivity, and an all-solid-state battery including the membrane can exhibit improved life characteristics.

Claims

1. A solid electrolyte composition for an all-solid-state battery, comprising: Solid electrolytes, binders and dispersants, in, The dispersant is a carboxylic acid compound having a weight average molecular weight of 1,000 to 5,000.

2. The solid electrolyte composition according to claim 1, in, The particle size D of the solid electrolyte 50 0.5 to 1.5 μm, particle size D 99 3 to 5 μm, and Among them, in the solid electrolyte composition for all-solid-state battery, the dispersed particle size D of the solid electrolyte is 50 0.5 to 1.5 μm, dispersed particle size D 99 3 to 5μm.

3. The solid electrolyte composition according to claim 2, in, In the solid electrolyte composition for all-solid-state batteries, the dispersed particle size D of the solid electrolyte is 99 / Dispersed particle size D 50 The ratio is 2 to 7.

4. The solid electrolyte composition according to claim 1, in, The dispersant is one or more selected from the group consisting of glycolic acid ethoxylate lauryl ether, glycolic acid ethoxylate oleyl ether and glycolic acid ethoxylate 4-tert-butylphenyl ether.

5. The solid electrolyte composition according to claim 1, in, The solid electrolyte composition for an all-solid-state battery includes 95 to 99 wt % of a solid electrolyte, 0.5 to 5 wt % of a binder, and 0.1 to 2 wt % of a dispersant, based on the total weight of the solid electrolyte composition for an all-solid-state battery.

6. The solid electrolyte composition according to claim 1, in, The solid electrolyte includes one or more selected from the group consisting of a sulfide-based solid electrolyte, a polymer-based solid electrolyte, and an oxide-based solid electrolyte.

7. The solid electrolyte composition according to claim 6, in, The solid electrolyte includes a sulfide-based solid electrolyte.

8. A solid electrolyte membrane for an all-solid-state battery, which is manufactured using the solid electrolyte composition for an all-solid-state battery according to claim 1.

9. The solid electrolyte membrane according to claim 8, in, The solid electrolyte membrane has a thickness of 20 μm to 50 μm.

10. The solid electrolyte membrane according to claim 8, in, The ionic conductivity of the solid electrolyte membrane is 1.3×10 -3 S / cm or more.

11. An all-solid-state battery comprising: a positive electrode, a negative electrode and a solid electrolyte membrane interposed therebetween, in, The solid electrolyte membrane is the solid electrolyte membrane according to claim 8.

Citation Information

Patent Citations

  • Solid electrolyte composition, sheet for all-solid-state secondary battery and all-solid-state secondary battery, and method for manufacturing sheet for all-solid-state secondary battery and all-solid-state secondary battery

    KR1020210134748A

  • Method for detecting a failure of at least one component of a continuous analysis monitoring system

    KR1020230078642A